Impacts of the conservation education program in Serra Malagueta Natural Park, Cape Verde. Issue 4 (18th May 2016) - Burnett, Edmund; Sills, Erin; Peterson, M. Nils; DePerno, Christopher
Abstract : Environmental and conservation education programs are commonly offered in the rapidly expanding network of protected areas in developing countries. There have been few evaluations of these programs and their impacts on participants. At Serra Malagueta Natural Park in Cape Verde, we assessed changes in environmental knowledge, opinions, and behaviors among visiting school children and a comparison group that did not visit the park. Participation in the park's conservation education program has a positive impact on environmental knowledge after the visit. The program may also contribute to student knowledge by influencing classroom teaching in anticipation of the park visit.